Advanced business services in emerging Asian economies - Klimek, Artur (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The goal of this paper is to present the results of the empirical analysis of the role of emerging Asian economies in the global market for business services. The focus is on India, as the leader in advanced business services in the region. The method applied in this paper is the quantitative analysis of data related to trade and foreign direct investment in services. The novelty of the paper lays in focusing on business services through their international exchange and activities of multinational corporations. This papers aims to focus on broader economic perspective rather than usual offshoring. The main conclusion of the paper is the rising role of services in economies that were previously focused on manufacturing and merchandise trade. Both due to the structural changes in foreign markets and home governments’ policies the process of tertiarisation is taking place. Special focus is on advanced business services which require and create vast amount of knowledge
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 61-70
Keywords: Asia; India; advanced business services; exports; foreign direct investment; Azja; Indie; zaawansowane usługi biznesowe; eksport; bezpośrednieinwestycje zagraniczne